Low-energy Ar+ ion-beam-induced chemical vapor deposition of silicon dioxide films using tetraethyl orthosilicate - Satoru Yoshimura; Satoshi Sugimoto; Takae Takeuchi; Masato Kiuchi (Heliyon, 2023)
This study was conducted to determine whether the simultaneous injections of Ar+ ions and tetraethyl orthosilicate (TEOS) to a substrate are able to fabricate a film on the substrate. The Ar+ ion energy was 100 eV. After the injections, we found a film deposited on the substrate. Following the analyses of the film with X-ray photoelectron spectroscopy and Fourier transform infrared spectroscopy, it was found that the deposited film was silicon dioxide (SiO2). We conclude that the low-energy Ar+ ion-beam-induced deposition method using TEOS is useful for the growth of SiO2 films.